2D Polymers as Emerging Materials for Photocatalytic Overall Water Splitting. Issue 48 (22nd July 2018) - Wang, Lei; Zhang, Ying; Chen, Liang; Xu, Hangxun; Xiong, Yujie
Abstract: Converting solar energy into storable and transportable chemical fuels using artificial photosynthetic systems can provide an alternative route to the current unsustainable use of fossil fuels, addressing the worldwide energy crisis and environmental issues. Recently, semiconducting polymers have emerged as a very promising class of photocatalysts for water splitting as their electronic and structural properties can be conveniently controlled and systematically designed at a molecular level. Among the various polymer photocatalysts that are reported so far, 2D polymer nanosheets are particularly interesting and gaining more attention. The 2D planar structure offers unique features such as high surface area, abundant surface active sites, efficient charge separation, and facile formation of heterostructures. The design and synthesis of 2D polymer nanosheets have greatly advanced the research in photocatalytic overall water splitting. Here, recent advances in developing photocatalysts based on 2D polymer nanosheets for photocatalytic overall water splitting are highlighted. Specifically, the existing approaches to tune their electronic structures and surface active sites for photocatalysis are discussed. Future opportunities and challenges for developing 2D polymers for photocatalytic overall water splitting are also included. Abstract : 2D polymer nanosheets have received increasing attention in converting solar energy into chemical fuels due to their tunable electronic and optical properties. Recent progress in developing heterogeneous photocatalysts based on polymer nanosheets for overall water splitting is reviewed. 2D polymer nanosheets are shown to be very promising for solar fuel generation using sunlight as the only energy input.